Wildlife sighting in cacao plantations in the North Zone, as an added value to the productive system - Carvajal-Alfaro, Vanessa (2022)
One of the sectors most affected by the pandemic caused by COVID-19 has been the tourism sector, which has generated not only unemployment but also the closure of many companies that were engaged in this activity. In order to diversify the tourist, offer of cocoa producers in the Upala region, since some farmers, in addition to offering their cocoa production, also offer some services such as guided tours to appreciate the production process and artisan production of cocoa products. Due to this, this project aimed to carry out an inventory of mammals and birds in three cocoa farms in the Upala region for the diversification of the tourist offer through the observation of birds and mammals as a differentiating element of the guided tours. in the farms, which would allow adding value to the service provided, as well as establishing a protocol for observing wildlife in the event of possible zoonoses. To meet this objective, several visits were made to each of the farms analyzed for the sighting of fauna and to analyze the production process. In these visits it was determined that the sampled farms have potential for the observation of emblematic wild mammals, mainly three-toed sloth and howler monkeys, while one of them can be used for bird watching with educational potential and experimental work.